MARCH 2013 PLACEMENT ADS (The Accounting Review, 2013)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for up-to-date, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.FAYETTEVILLE STATE UNIVERSITY, The School of Business and Economics is seeking a tenure track Assistant/Associate Professor to join our well-regarded Accounting Department, beginning Fall 2013. Candidates should have a Ph.D. degree from an AACSB-accredited school. ABDs are encouraged to apply. The person hired will be expected to teach financial accounting, managerial accounting, and/or auditing. A constituent institution of the University of North Carolina system, The School of Business and Economics at Fayetteville State University is considered one of the leading business schools in its region. The SBE has an enrollment of approximately 1,000 undergraduate and M.B.A. students. The School has regularly been featured in The Princeton Review, is AACSB-accredited, and is ranked by the Social Science Research Network (SSRN) as one of the top 100 business schools in the United States and one of the top 5 in North Carolina. Please submit a letter of interest, a curriculum vitae, copy of graduate transcripts, and contact information of three professional references to: http://jobs.uncfsu.edu/postings/5932WESTERN NEW ENGLAND UNIVERSITY invites applications for a tenure-track Assistant/Associate Professor accounting position to begin August 2013. Candidates are expected to hold a Doctorate in Accounting or anticipate having completed all degree requirements by the starting date. The successful candidate will demonstrate a strong commitment to teaching in the undergraduate and graduate programs and to publishing scholarly research. An interest in teaching financial accounting or auditing is desirable. Western New England University is a private, independent, coeducational institution founded in 1919 and located on an attractive 215-acre suburban campus in Springfield, Massachusetts within easy access of Boston and New York City. More information about the University is available at http://www.wne.edu. Send curriculum vitae, teaching evaluations, research manuscript, and reference information to: Dr. Julie Siciliano, Dean, College of Business, Western New England University, 1215 Wilbraham Road, Springfield, MA 01119. Electronic submissions are encouraged and should be sent to lori.fenton@wne.edu. Western New England University is an Equal Opportunity Employer.WEBSTER UNIVERSITY invites applicants for a nine-month tenure-track faculty position at the rank of Assistant Professor. Salary is competitive with other private AACSB-accredited institutions in the Midwest. Teaching Responsibilities: The candidate will have responsibilities with respect to teaching undergraduate and graduate accounting courses in financial accounting and corporate and personal income tax accounting. This position also offers teaching opportunities at Webster's international network of campuses. Other responsibilities will include research activities and department and university service. The desired candidate will possess a Ph.D. in accounting from an AACSB-accredited business school and experience teaching in graduate and undergraduate business programs. Webster values faculty with practical work experience, and a faculty with experience in teaching is desired. Contact Arnoldo Rodriguez at: SBTFacultySearch@webster.edu; or Phone: (314) 246-5992.MANHATTAN COLLEGE, School Of Business, an AACSB-accredited school, seeks applicants for a tenure track position in Accounting, beginning in Fall 2013. Rank will be commensurate with qualifications. Candidates must have a Ph.D. or D.B.A. in Accounting or in a related field. (Applicants expecting a doctoral degree relatively soon will be considered as well.) Candidates must provide evidence of teaching effectiveness and research accomplishments. Responsibilities include teaching undergraduate and graduate courses in Accounting and engaging in scholarly activities and participating in campus activities. The Department seeks candidates with expertise in tax, IT auditing, and accounting systems, but all qualified candidates are encouraged to apply. Interested candidates should submit: a letter of application, a cv, evidence of teaching effectiveness, a sample of current research, and three letters of references. All materials should be submitted to Dr. Mehmet Ulema at mehmet.ulema@manhattan.edu, subject line: Accounting Position. Application review will begin immediately and continue until the position is filled. Manhattan College is an independent Catholic Coeducational institution in the LaSallian tradition located in the Riverdale section of New York City (http://www.manhattan.edu). We expect our faculty, administration, and staff to be knowledgeable about our mission and to make a positive contribution to that mission. Women and minorities are encouraged to apply. We are committed to a diverse campus community. AA/EO Employer M/F/D/V.YORK UNIVERSITY, Faculty of Liberal Arts and Professional Studies School of Administrative Studies (1 position in the area of Accounting) Applications are invited from qualified candidates for a full-time tenure-stream Assistant Professor position in the area of Accounting. Applications are welcome from either financial or managerial accounting disciplines. A Ph.D. in Accounting (or near completion) is required, as is evidence of excellence, or the promise of excellence, in both teaching and scholarly research. Preference will be given to those with a professional designation in accounting and those who have university teaching experience at both undergraduate and graduate levels. The successful candidate will be expected to participate in both the undergraduate and graduate programs. Ability to teach in multiple areas of accounting would be deemed an asset. Successful candidates must be suitable for prompt appointment to the Faculty of Graduate Studies. The start date is July 1, 2013. All York University positions are subject to budgetary approval. The deadline for all positions is February 15, 2013. Candidates should submit a signed letter of application (indicating the position for which they are applying), an up-to-date curriculum vitae, a statement of specific teaching and research interests, summaries of teaching evaluations (if available), and the names of three referees, and arrange for three reference letters to be sent directly, to: Professor Peggy Ng, Director, School of Administrative Studies, 223 Atkinson, York University, 4700 Keele St., Toronto, Ontario, Canada, M3J 1P3. All qualified candidates are encouraged to apply; however, Canadian citizens and permanent residents will be given priority. York University is an Affirmative Action Employer. The Affirmative Action Program can be found on York's website at http://www.yorku.ca/acadjobs or a copy can be obtained by calling the affirmative action office at (416) 736-5713.RUTGERS, THE STATE UNIVERSITY OF NEW JERSEY and AAU Member University, seeks applicants to full-time, non-tenure track instructor positions within Rutgers Business School Newark and New Brunswick to teach large classes (ranging from 100 to 450 students) for courses in Financial Accounting and Managerial Accounting. Applicants for these positions must have demonstrated excellence in teaching large classes and must have qualifications to meet AACSB-accredited (the business school accrediting body) standards for either academic or professional qualifications. Ph.D. desirable, ABD acceptable, minimum Master's degree in area of teaching responsibility or Masters degree combined with significant managerial experience. Please, direct any inquiries to email. Applications will be accepted until the positions are filled. Contact Valentin Dimitrov at: vdimitr@rutgers.edu; or Phone: (973) 353-1131.THE UNIVERSITY OF IOWA, The Department of Accounting, Tippie College of Business, University of Iowa, Iowa City, Iowa, invites applicants for a tenure-track appointment(s) beginning Fall 2013. We will consider candidates at all ranks. Required qualifications include a demonstrated interest in and capacity to do research publishable in top-tier accounting journals, a high level of teaching competence, and an earned doctorate (entry-level candidates can be near completion). We offer a competitive compensation package. We will screen applicants at all ranks on an ongoing basis. To apply, please log on to our website, http://jobs.uiowa.edu/jobSearch/faculty/ and reference Requisition #61273. You will be asked to upload a résumé, representative research output, evidence of teaching capabilities (if available); and to provide the names for at least three letters of recommendation. The University of Iowa is an Affirmative Action/Equal Opportunity Employer. Women, minorities, and individuals with disabilities are encouraged to apply.DONGBEI UNIVERSITY OF FINANCE AND ECONOMICS (DUFE), China seeks applicants for Assistant Professor, Associate Professor, Research Fellow, and Lecturer. Job duties for a successful applicant will include research, teaching (which is not required if applying for a researcher position), and service to the School and University as full-time staff member. BENEFITS: The annual salary will be RMB 300,000 or above, plus health insurance, housing accumulation funds, temporary housing (or housing allowances), traveling expenses for international conference, research grant, and Ph.D. allowance. Rank, extra awards, and funds will be granted depending on research experience and performance. Additionally, private office and necessary research resources are available. Candidates must have a completed Ph.D. degree in accounting or corporate finance from a prestigious overseas university and concentrate on the research of accounting, auditing, or corporate finance. Contact Qi Yuan at: qiyuan@dufe.edu.cn.UNIVERSITY OF PITTSBURGH, The Joseph M. Katz Graduate School of Business and College of Business Administration seeks applications for an anticipated tenure-track Assistant Professor position in the accounting area starting Fall 2013 (contingent on budgetary approval and upon authorization to work in the United States). The appointment requires a strong commitment to excellence in scholarly research and teaching. All areas of accounting are appropriate, but preference will be given to experimental researchers. Applications must be submitted electronically to: http://www.katz.pitt.edu/facultyhiring/accounting-ts.php. Materials submitted must include a letter of interest, vitae/resume, sample research paper(s), evidence of teaching effectiveness, and three letters of reference. Application deadline is January 15, 2013. Please apply online to the website listed above, but questions about the position can be directed to accfacultysearch@katz.pitt.edu. The University of Pittsburgh is an Affirmative Action, Equal Opportunity Employer and values equality of opportunity, human dignity, and diversity.BONAVENTURE UNIVERSITY, The Department of Accounting at invites applications for a tenure-track position at the Assistant or Associate Professor level. The successful candidate will teach undergraduate and graduate courses, predominantly in the area of Financial Accounting and/or Audit. The candidate will also be expected to undertake scholarly research in a collaborative environment that welcomes inter-disciplinary and practice-oriented scholarship, as well as discipline-based and theoretical work. The position appointment is expected to begin with the Fall 2013 semester, contingent upon funding. Applicants must meet the following required qualifications: (1) earned doctorate in accounting or related field by the time of appointment; (2) demonstrated excellence in teaching and willingness to work closely with students in curricular and co-curricular activities, including service, professional and/or research activities; and (3) an established or emerging research program. Accounting certification and prior professional accounting experience are preferred. St. Bonaventure University is the nation's premier Franciscan university. The School of Business, AACSB-accredited, will be moving into its new state-of-the-art Swan Business Center home in Fall 2013. Accounting faculty, students, and programs also benefit from the endowed McQuade Center for Accounting Excellence. The Department of Accounting offers two program tracks: a 120-hour B.B.A. in Accounting and a 150-hour B.B.A./M.B.A. program in Accounting registered for CPA Exam qualifications. Our B.B.A./M.B.A. graduates are highly recruited by Big 4 CPA firms and other large employers. Applications may be submitted online at: accountingsearch@sbu.edu. For additional information please contact the department chair, Dr. Susan B. Anders at sanders@sbu.edu or (716) 375-2063. Dr. Anders will be in attendance at the AAA Annual Meeting in Washington, DC. Review of applications will begin immediately and continue until the position is filled. The University, School, and Department have a strong commitment to achieving diversity faculty and and applications from of OF has available a tenure-track position as or Professor of Accounting available August 2013. The candidate will have an interest in teaching Required qualifications include a in Accounting from an AACSB-accredited institution near degree will be or an in an accounting from an for excellence in to publishable and evidence of strong and Professional certification preferred. applications by February 1, 2013 will be given Candidates must apply To apply, For more information please contact Dr. Accounting Phone: The University is an Equal Opportunity Employer with a for Affirmative OF School of seeks qualified candidates for two full-time teaching positions Assistant in Accounting in and Financial Accounting or program at its New York campus The applicant must hold a Ph.D. (or be from an AACSB-accredited institution and have demonstrated in within the area of and a demonstrated commitment to service to students and the community. with and is highly Salary is commensurate with qualifications. candidates will be expected to teach courses in accounting and related areas in the and Master's research, in journals, students and participate in the faculty including for students and community. School of offers degree programs at the and level. More information about the school and current faculty can be found at Interested candidates should cv, electronically to Dr. Phone: on the of and is committed to OF Department of Accounting of the College of Business an AACSB-accredited invites applications for two positions of Assistant or Associate Professor of Accounting, beginning August 2013. Applicants must possess or be of a doctoral degree in accounting, from an AACSB-accredited and have a strong commitment to excellence in both teaching and research. We welcome candidates with research in any area of accounting, with preference for one of the positions to be by a candidate with teaching experience and interest of financial accounting. We who will scholarly research and teaching at both the undergraduate and graduate levels. Salary and are The University of is one of the of the University of and a diverse of the of St. The AACSB-accredited College of Business Administration offers undergraduate and graduate a of programs and in a of business disciplines. The Accounting program a of Science in Accounting and a of Accounting. applicants should submit a letter of interest and a current including evidence of teaching electronically to Associate Professor of Accounting at with subject reference to the specific either or UNIVERSITY OF invites applications for a tenure-track Rank is and the expected start date is Fall 2013. duties include teaching and graduate courses in engaging in research and activities in the accounting and that to in journals, and other of and service to the School of the College of Business the University, and the professional community. is a Ph.D. in accounting from an AACSB-accredited institution or or candidates with an or may also be For and to apply please Job OF School of is seeking applications for a tenure-track Assistant Professor faculty position in the area of for Fall 2013. Candidates must have a teaching interest in and be committed to scholarly research. Applications are encouraged from Assistant as well as new or those of Ph.D. Salary and research are Application Application materials including a letter of interest, curriculum vitae, evidence of teaching competence, and a sample of should be submitted online at reference letters should be to: School of University of or to will begin immediately and continue until the position is filled. The University of is an Equal Action Employer. Applications from and candidates are encouraged for this To please contact the at UNIVERSITY, AACSB-accredited accounting program invites applications for a tenure-track Assistant Professor position in Accounting, beginning August 15, 2013. doctorate (or ABD with expected work is and Teaching areas about the position and application are available at: University is an Equal Opportunity OF Department of Accounting in invites applications for a tenure-track faculty position at the Assistant/Associate Professor The for this is with preference for financial accounting, accounting information systems, or The Department of Accounting at offers a of academic degree programs including of Accounting professional program in or Accounting, in or Accounting, and an Accounting doctoral program. Our programs are the in the our faculty expertise in a of accounting and the department is Candidates must hold a doctorate in accounting (or and demonstrate excellence in a strong publication Associate or a strong publication Assistant Candidates for the Assistant Professor must have completed all doctoral degree requirements by start of and to the standards of and teaching or certification is but not The Department of Accounting is committed to academic excellence and diversity within our faculty, and at: UNIVERSITY, School of Business, The Department of of invites applications for a tenure-track position at the Assistant Professor level to begin Fall 2013. Applicants must have a Ph.D. in accounting or a related field. ABD candidates will be considered but must all doctoral degree requirements by August 1, 2013. Applicants must demonstrate research as by in top or in and teaching excellence as by letters of reference and teaching Application To be please the online faculty application at: and upload a current curriculum vitae, to three and teaching evaluations, if available. letters of reference must also be to the Department of The University School of Business, Washington, applications will be Review of applications will begin on January 2013 and will continue until the position is filled. The University is an Equal Action Employer. The University and the School of Business to an and diverse faculty of the OF Accounting School of Business, The School of Business at the University of seeks applicants for an Assistant or Associate Professor of Accounting. This is a full-time, tenure-track position with a start date of August 2013. The successful candidate will participate in service, and as to the field of accounting. The candidate should have a strong of teaching excellence at the undergraduate level for both accounting and The to teach financial and managerial accounting, accounting, and accounting information is Teaching is also Candidates should have an earned doctorate in accounting or closely related business field for this tenure-track ABD candidates may apply. qualified candidates with an may be considered for a Candidates must have demonstrated in teaching and of the accounting field. and in the are electronically at: Review of applications will begin immediately and continue until the position is filled. The University of is an Affirmative Action/Equal Opportunity and applications from and STATE UNIVERSITY seeks Candidates for Associate or Assistant Professor level. Candidates are required to hold or be near of an earned doctorate in accounting or in business with in accounting from an AACSB-accredited business school. Candidates for Associate Professor are required to have an established of teaching and research. and current professional certification in accounting preferred. The successful applicant will have responsibilities in teaching and research and service to the and community. The position requires scholarly including research in accounting Candidates with teaching in all areas of accounting will be The will be business and accounting by The University is the institution and has approximately campus students. Preference will be given to candidates who can provide evidence teaching and a publication and/or for level of academic experience. Application letter of application, current graduate transcripts, and a of three that may be for reference. Review of applications will begin Dr. New State University, New Phone: UNIVERSITY, College of Business Administration is seeking applications for a tenure-track faculty position at the rank of Assistant Professor beginning August 1, 2013. Job responsibilities include teaching undergraduate and graduate courses in accounting. Applicants will be to teach courses as well as and accounting in an Preference will be given to applicants with professional accounting experience. A Ph.D. or significant a degree in accounting from an AACSB-accredited institution is teaching experience is preferred. Applicants must demonstrate the and interest in high that will the accounting community. all an program with significant University is seeking applicants who can demonstrate the interest and to work in and to teach and courses in this program. for additional information and for the online The university seeks a person of and commitment to the mission of the university. A coeducational university located in is a university on academic University is an Equal Opportunity Employer committed to a diverse of committed from all and OF School of Business invites applications for multiple tenure-track positions in Accounting at the rank of Professor. The is A new program in the to an accounting track to its new Ph.D. in Business Administration in 2013 and to a new state-of-the-art within the three with an diverse of approximately is located about of An earned Ph.D. or D.B.A. in accounting or a related by the starting date 2013 or A demonstrated or at the level a strong research. A demonstrated of in of Accounting, or at both the graduate and undergraduate levels. and the to and The to work with a diverse and faculty given to candidates with accounting or corporate experience, with Applicants should apply online at: a (1) a statement of professional and (2) cv, (3) of research, teaching and evidence of teaching Applications accepted until the posting is UNIVERSITY, Department of Accounting invites applications for a tenure-track position at the Assistant or Associate level beginning in Fall 2013. is a private, highly university located in the The School of and has been AACSB-accredited Job Applicants should have a doctorate or be to and have teaching in auditing. to applicants are expected to research publishable in To research, the school to available Application Candidates should electronically submit a curriculum vitae, evidence of teaching effectiveness and scholarly and three letters of reference to: questions about the position should be sent to Dr. who is the Application review will begin University is an Equal Action STATE UNIVERSITY, College of Business seeks applications for a full-time, tenure-track Professor of Accounting for its Department of Accounting. The teaching area is accounting. date is Fall 2013. Salary is competitive and commensurate to experience and qualifications and package. Responsibilities: Teaching a of accounting courses in areas of Financial Accounting, Managerial Accounting or at the undergraduate and graduate level including online to the Center may be scholarly work and service are State College of Business is AACSB-accredited and values scholarly and service. ABD candidates with a date will be considered for appointment at the rank of teaching experience and evidence of scholarly work are doctorate in Accounting or related field. Accounting experience and professional are desired. Application review to begin applications until 2013. To apply, a letter of interest, and the and of three professional to: Professor of in the subject State University welcomes and and minorities to apply and seeks to and a diverse is an Equal Opportunity Employer. and for qualified individuals with will be upon Please in UNIVERSITY invites applications for a tenure-track Assistant or Associate Professor position in accounting beginning Fall 2013. is applications or auditing but other areas may be The position is subject to degree in accounting or by the appointment academic or professional and strong teaching and research or demonstrated are include teaching undergraduate and graduate courses, University service, and scholarly Western is located and and the of The University has students and the College is Applications must include a letter of application how qualifications are cv, evidence of teaching effectiveness, transcripts, and names of three references. All application materials must be the Electronic Application for at: